2019
DOI: 10.1111/jasp.12620
|View full text |Cite
|
Sign up to set email alerts
|

Need for closure effect on collective action intentions and behavior toward immigrants in Italy: The mediation of binding foundations and political conservatism

Abstract: Why are people (de)motivated to mobilize in favor of immigrants? Addressing this question, we investigated the role of individuals' epistemic motivation (i.e., need for closure) in influencing the process of becoming motivated to participate in collective action in favor of immigrants in Italy. Specifically, the mediational role of binding moral foundations and political conservatism in explaining the relationship between need for closure and collective action in favor of immigrants was examined in three studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
3
18
0
Order By: Relevance
“…Literature in the field attests that bonding networks are resourceful means to get settled within the resettlement communities as they provide for housing, job opportunities but also with emotional and social support (Beirens et al, 2007; Calhoun, 2010; Eriksson et al, 2018). These results go in the same line and beyond as they testify that the creation of bonding networks, through the use of ICT, is intended by JOIN as a mean to create a collective action, or rather an action undertaken by a group in order to improve a disadvantaged situation (Hovland & Sears, 1940 in De Cristofaro et al, 2019). At the same time, both the web platform and social media will spread positive narratives about refugees that will act as a glue for the creation of bridging networks.…”
Section: Resultsmentioning
confidence: 57%
“…Literature in the field attests that bonding networks are resourceful means to get settled within the resettlement communities as they provide for housing, job opportunities but also with emotional and social support (Beirens et al, 2007; Calhoun, 2010; Eriksson et al, 2018). These results go in the same line and beyond as they testify that the creation of bonding networks, through the use of ICT, is intended by JOIN as a mean to create a collective action, or rather an action undertaken by a group in order to improve a disadvantaged situation (Hovland & Sears, 1940 in De Cristofaro et al, 2019). At the same time, both the web platform and social media will spread positive narratives about refugees that will act as a glue for the creation of bridging networks.…”
Section: Resultsmentioning
confidence: 57%
“…However, there has lately been a rapidly growing interest in how moral intuition, an immediate and non-argumentative form of moral judgment based on these two sets of moral foundations (Haidt, 2012) can explain intergroup attitudes and preferences. So far, studies have shown that individualizing foundations are related to more positive attitudes and binding foundations to more negative attitudes toward outgroups like Muslims (Hadarics & Kende, 2018a;Kugler et al, 2014;Van de Vyver et al, 2016), immigrants (Baldner & Pierro, 2019;Hadarics & Kende, 2017;Van de Vyver et al, 2016), sexual outgroups (Barnett et al, 2018;Monroe & Plant, 2019), poor people (Low & Wui, 2016), beggers (Nilsson et al, 2016), or foreigners (Nilsson et al, 2020;Smith et al, 2014). Furthermore, moral foundations were also found to be related to more generalized dimensions of prejudice, like attitudes toward "dangerous," "derogated," and "dissident" groups (Forsberg et al, 2019;Hadarics & Kende, 2018b).…”
Section: Moral Values and Intergroup Attitudesmentioning
confidence: 99%
“…Gray and colleagues (e.g., Schein & Gray, ) have argued that perceived harm underlies moral violations, even for so‐called “harmless” crimes (e.g., “disrespecting” the flag). Regardless of the underlying factors, the moral foundations have previously been used as a series of attitudes toward different types of norm violations (e.g., Baldner & Pierro, , ; De Cristofaro et al, ).…”
Section: Introductionmentioning
confidence: 99%